High dietary zinc and glutamine do not improve the performance or reduce excreta moisture of broiler chickens fed diets with and without magnesium supplementation. (7th March 2019) - Barekatain, R; Toghyani, M
ABSTRACT: An experiment was conducted to investigate the effect of supplemental L-glutamine (L-Gln) and a higher concentration of zinc (Zn) on excreta moisture under nutritionally induced wet droppings via decreased intestinal water reabsorption. A 2 × 2 × 2 factorial arrangement of treatments was used to investigate 3 dietary factors of L-Gln supplementation (0 or 10 g/kg), and added Zn concentration (80 and 160 mg/kg) with or without magnesium chloride (MgCl) (2 g/kg—only in grower diets). A total of 576 male day-old Ross 308 broiler chickens were assigned to the experimental diets. Each diet was replicated 6 times with 12 birds per replicate. Wheat-based diets were formulated to be isocaloric and isonitrogenous. Starter diets were given from day 0 to 9 followed by grower (day 10 to 23) and finisher diets (day 24 to 35). Excreta moisture was measured for all the growth phases. The moisture content of different segments of intestine was assessed for starter and grower phases of feeding. There was no significant effect of any of the 3 main treatments on body weight gain or feed intake of birds during the experiment. Birds fed higher Zn (160 mg/kg) tended ( P = 0.09) to have higher weight gain only in the first 9 days of age. Feeding 10 g/kg L-Gln increased the feed conversion ratio of the birds only from hatch until day 9 after which there was no significant effect. No effect of experimental treatments was found on digesta or excreta moisture, except a reduction in ileal moisture at the starter phase resulting from higher Zn concentration in the diets. MgCl at 2 g/kg was not effective in inducing wet droppings in birds fed grower diets. Under the conditions of this study, no positive response was observed in terms of performance or reduction in excreta moisture when birds were fed diets containing 10 g/kg L-Gln or higher concentration of Zn.